Validation of a Motor Competence Assessment Tool for Children and Adolescents (KTK3+) With Normative Values for 6- to 19-Year-Olds - Coppens, Eline; Laureys, Felien; Mostaert, Mireille; D'Hondt, Eva; Deconinck, Frederik J. A.; Lenoir, Matthieu (Frontiers in Physiology, 2021)
The use of the short form of the Körperkoordinationstest für Kinder (KTK3) to evaluate children's and adolescents' motor competence (MC) is increasing. When combined with an alternating one-handed catching and throwing ball task, assessing eye-hand coordination (EHC), it has been shown that the different aspects of motor skills are adequately covered in one compact KTK3+ test battery, studied in 6- to 10-year-old children. The present study aimed to validate the KTK3+ test battery and to provide contemporary MC normative values for boys and girls from 6- to 19-year-olds. A total of 2,271 children and adolescents (1,112 boys, 1,159 girls) participated in this study and were evaluated on the four included test items: jumping sideways (JS), moving sideways (MS), balancing backwards (BB), supplemented by an EHC task. Children's participation in organised sport was registered using a demographic questionnaire. For the first objective, a factor analysis with multidimensional scaling demonstrated that the one-dimensional model provided the best fit, with all test items correlating to the same latent construct: “MC”. This was further supported with moderate to good correlations between all four test items (r = 0.453–0.799). Construct validity was investigated with a three-way MANOVA, demonstrating a significant multivariate interaction effect between sex and age group (p = 0.001) as well as a multivariate main effect of sex, age group, and organised sport participation (p < 0.001). Boys outperformed girls on two out of the four tests (JS and EHC, p < 0.005), while girls were better than boys on the BB test (p < 0.005). Performance scores increased across age groups on all tests (p < 0.001). Only for the BB test score, a plateau effect was noted around the age of 12 years. Children and adolescents participating in sports generally outperformed their peers who were not involved in organised sports, on the present KTK3+ test battery. For the second objective, raw score normative values are provided separately for both sexes between 6- to 19-year-olds. In combination with the one-factor structure confirmation, these sex, age, and sport participation effects demonstrate the validity of the test battery. The provided normative values are useful to evaluate MC in children and adolescents from 6 to 19 years old. The use of only four test items that are identical across all ages makes the KTK3+ test battery a practical instrument to assess and compare MC development.